The effect of the combination of volume and technique of administering nutrient solution on the growth and yield of large red chili plants (Capsicum annum L) baja F1 variety - Turmuktini, Tien; Azhari, Yolanda Dewi; Mulya, Agus Surya; Ria, Elly Roosma; Fitriatin, Betty Natalie; Simarmata, Tualar; Fauziah, Nicky Oktav; Muliani, Yenny (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: In Indonesia itself, it is estimated that red chilies were brought by traders from Persia when they stopped in Aceh, including large red chilies, cayenne peppers, curly red chilies, and paprika. Factors that influence chili cultivation are less fertile soil conditions due to continuous use, this causes a decrease in soil quality which will affect the growth and production of chili plants and have an impact on reducing the growth and yield of chili production both in terms of quantity and quality, in addition to the use of quality seeds and superior varieties determine the increase in chili productivity. Methods: This research was conducted out from May 2022 to September 2022 in the experimental farm of the Faculty of Agriculture, Padjadjaran University, Jatinangor, Sumedang. With an altitude of about 700 meters above sea level (masl). The purpose of this research is to study the effect of volume combination and technique of nutrient solution administration on growth and yield of large red chilies (Capsicum annum L.) variety Baja F1. Providing nutrient solutions on time is intended to be according to the age of the plant, the right volume is intended to provide nutrient solutions with a certain volume that suits the needs of each plant, while right on target is intended to provide nutrient solutions in the root area or sprayed on the leaves, either fertilizing directly to the land or plant roots or spraying directly on the leaves (foliar feeding). The environmental design uses a simple pattern randomized block design (RAK) volume combination and technique of nutrient solution, with 6 experimental levels (A=volume 225 ml onto the field and without spraying onto the leaves, B=volume 300 ml onto the field and without spraying onto the leaves, C=volume 375 ml onto the field and without spraying onto the leaves, D=volume 200 ml onto the field and spraying onto the leaves, E=volume 300 ml onto the field and spraying onto the leaves and F=volume 375 ml onto the field and spraying onto the leaves), and repeated 4 times. Findings: The application of different combinations of nutrient solution volume and administration techniques significantly affected several growth parameters (such as plant height at 3 WAP, number of leaves at 1, 2, 4, and 5 WAP, and stem diameter at 4 and 5 WAP) as well as yield parameters (including number of chilies and total fruit weight). Conclusion: Among the treatments, the combination of applying 225 ml nutrient solution directly to the field along with foliar spraying produced the most optimal results in terms of both growth and yield of Baja F1 chili plants. Novelty/Originality of this article: This study provides novel insights into the integrated approach of combining precise nutrient volume and foliar feeding techniques, specifically identifying the synergistic effect of 225 ml root application and foliar spraying in enhancing growth and yield, which has not been thoroughly explored in previous chili cultivation studies.